The Slight Transformation: Contesting the Legacy of Karl Polanyi - Lacher, Hannes (Palgrave, 2007)
[Abstract Not Available]
10th International Karl Polanyi Conference on Protecting Society and Nature From Commodity Fiction -- OCT 14-16, 2005 -- Univ Bogazici, Istanbul, TURKEY